2004
DOI: 10.1111/j.1360-0443.2004.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of brief cognitive–behavioural interventions for insomnia in recovering alcoholics

Abstract: Recovering alcoholics with insomnia can achieve better sleep by applying cognitive-behavioural strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 40 publications
7
138
3
2
Order By: Relevance
“…Although the impact of CBT-I or sleep medications on cannabis use cessation has yet to be thoroughly evaluated, research drawing from the treatment of alcohol use disorders provides some insight. Research has shown that among individuals recovering from alcohol dependence, behavioral interventions (e.g., CBT-I) improve self-reported and objective measures of sleep immediately after the intervention [65,66] and at 3 and 6 months after the intervention [65]. However, there has yet to be any documentation of an effect of behavioral sleep interventions on alcohol use cessation outcomes (e.g., abstinence, relapse) [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of CBT-I or sleep medications on cannabis use cessation has yet to be thoroughly evaluated, research drawing from the treatment of alcohol use disorders provides some insight. Research has shown that among individuals recovering from alcohol dependence, behavioral interventions (e.g., CBT-I) improve self-reported and objective measures of sleep immediately after the intervention [65,66] and at 3 and 6 months after the intervention [65]. However, there has yet to be any documentation of an effect of behavioral sleep interventions on alcohol use cessation outcomes (e.g., abstinence, relapse) [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of telephone consultation to self-help written material enhanced outcomes at post treatment, but those gains tended to disappear at follow up (Mimeault & Morin, 1999). Another study of insomnia in recovered alcoholics also found equivalent outcome between individual CBT and self-help CBT plus telephone consultation (Currie, Clark, Hodgins, & El-Guebaly, 2004). …”
Section: Insomnia 19mentioning
confidence: 99%
“…Likewise, there is preliminary evidence that treating insomnia in the context of cooccurring major depression (Manber et al, 2008;Taylor, Lichstein, Weinstock, Sanford, & Temple, 2007), generalized anxiety disorder (Blais, Mimeault, & Morin, 2000), or substance abuse (Arnedt et al, 2007;Currie, Clark, Hodgins, & El-Guebaly, 2004 Therapeutic effects were well maintained up to 12 months after the intervention. In a similar study targeting insomnia in 150 patients with various forms of cancer (Espie et al, 2008), treatment was implemented in small groups by oncology nurses; significant improvements of sleep and quality of life and reduction of daytime fatigue, were observed in patients treated with CBT relative to those who received treatment as usual.…”
Section: Insomnia 12 Treatment Of Comorbid Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…21 Although the number of sessions in this study were fewer than the 6 to 8 offered in traditional CBT-I, previous trials have indicated the efficacy of brief versions of CBT-I in patients with primary insomnia, older adults with chronic insomnia, and patients with alcoholism and insomnia. [22][23][24][25][26] The treatment regimen was highly structured and included modules on sleep hygiene education, an introduction to the behavioral model of insomnia, sleep restriction, stimulus control, sleep titration, and relapse prevention. 16 Five psychiatrists and a psychiatric nurse provided the psychotherapy, and they received a written manual describing the regimen.…”
Section: Study Design and Interventionsmentioning
confidence: 99%